Geographical etymology: a dictionary of place-names giving their derivations - Blackie, Christina, 1808-; Blackie, John Stuart, 1809-1895 (Salt Lake City, UT : Project Gutenberg, 2022)
"Geographical Etymology: A Dictionary of Place-Names Giving Their Derivations" by C. Blackie is a scientific publication written in the late 19th century. The book is a comprehensive exploration of the etymology of geographical names, aiming to illuminate the connections between the names of places and their historical and geographical contexts. This work is particularly relevant for students and educators in geography and history, as well as for anyone interested in the origins and meanings of place names. The opening of the dictionary presents an introduction that highlights the importance of etymology in understanding the significance of place names. C. Blackie argues that knowledge of the origins of these names is essential not only for academic study but also for enriching the experience of travelers. He reflects on his own educational background, pointing out the lack of emphasis on etymology in teaching geography and history, and expresses concern that many names and their meanings have been lost or neglected. The section sets a foundation for the subsequent detailed entries in the dictionary, which will likely delve into various place names and their derivations, illustrating the rich tapestry of language and history that defines geographical locations. (This is an automatically generated summary.)
First published under title: Etymological geography.
Release date is 2022-09-20
Brian Coe, Karin Spence. The book cover image was created by the transcriber and is placed in the public domain, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Names, Geographical